Free simulation software "Swimsuit" to learn and research biomechanics in swimming - Nakashima, M. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The authors have developed a simulation model "SWUM" (Nakashima et al., 2007) and its implementation software "Swumsuit". Since the software was reported on the last symposium, it has been updated successively in order to extend its possibility. In this pool side demonstration, its technical description as well as the basic usage will be presented in order to show its usefulness for learning and researching the biomechanics in swimming, while the scientific results will be presented in another oral presentation (Nakashima et al., 2010). METHODS: Swumsuit was written in two programming languages. For the main simulation program, the programming language FORTRAN was employed because of its high computing performance in numerical calculation. For the graphical user interface, the script language Tcl/Tk was employed because of easiness for constructing the graphical user interface. RESULTS AND DISCUSSION: Swumsuit is an open source free software and available on the website (http://www. swum.org/swumsuit/). It runs on Windows, Macintosh and Linux. The current version is 4.0.2. From the version 2.0.0, 3.0.0, and 4.0.0, the optimizing calculation, musculoskeletal simulation, and multi agent/ object simulation have been enabled, respectively. For optimizing calculation, the user can describe freely the design variables and objective function by writing scripts. For the musculoskeletal simulation, the user can invoke the musculoskeletal software from Swumsuit directly. For the multi agent/object simulation, the user can describe the mechanical interaction between the agents/objects. Participants for this session are recommended to bring their own laptop computers since the software and sample data of the above results will be distributed by CD-R or USB memory in the session in order to enable the participants to use the software by themselves.